2015
DOI: 10.1073/pnas.1500869112
|View full text |Cite
|
Sign up to set email alerts
|

Memory formation and retrieval of neuronal silencing in the auditory cortex

Abstract: Sensory stimuli not only activate specific populations of cortical neurons but can also silence other populations. However, it remains unclear whether neuronal silencing per se leads to memory formation and behavioral expression. Here we show that mice can report optogenetic inactivation of auditory neuron ensembles by exhibiting fear responses or seeking a reward. Mice receiving pairings of footshock and silencing of a neuronal ensemble exhibited a fear response selectively to the subsequent silencing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Examining the cortical regions involved in auditory processing of a CS, Nomura et al (2015) demonstrated that unilateral optical inhibition of the auditory cortex is sufficient to act as a CS for both positive and negative valence training paradigms 58 . This study highlights the need to consider interoceptive stimuli as possible confounding variables in studies utilizing optogenetic activation and silencing manipulations.…”
Section: Optogenetic Tracing Of Fear Circuitrymentioning
confidence: 99%
“…Examining the cortical regions involved in auditory processing of a CS, Nomura et al (2015) demonstrated that unilateral optical inhibition of the auditory cortex is sufficient to act as a CS for both positive and negative valence training paradigms 58 . This study highlights the need to consider interoceptive stimuli as possible confounding variables in studies utilizing optogenetic activation and silencing manipulations.…”
Section: Optogenetic Tracing Of Fear Circuitrymentioning
confidence: 99%
“…First, the multiple trace theory states that in addition to activated cells during the user-defined time windows, non-activated cells would become the engram cells during memory consolidation and retrieval (Nadel et al, 2000 ). The actively inhibited cells involved in other processes of memory (Nomura et al, 2015 ; Vetere et al, 2021 ) should be appreciated during the formation of engram cells. Thus, labeling and manipulating inactivated cells around the activated cells is crucial for studying memory engrams.…”
Section: Discussionmentioning
confidence: 99%
“…Because this inhibition is necessary for content-specific memory retrieval success, these inhibited neurons ought to be considered a genuine component of the engram. Similarly, much as re-activating neurons that were active during encoding promotes memory retrieval, re-inhibiting neurons that were actively inhibited during encoding can also promote memory retrieval [ 191 ]. That such neurons are re-inhibited (rather than re-activated) during memory retrieval does not preclude them from being an essential component of the engram (for conceptually related work on inhibitory engrams, see [ 192 , 193 ]).…”
Section: Future Considerationsmentioning
confidence: 99%